Changes in biocrust cover drive carbon cycle responses to climate change in drylands. (11th September 2013) - Maestre, Fernando T.; Escolar, Cristina; de Guevara, Mónica Ladrón; Quero, José L.; Lázaro, Roberto; Delgado‐Baquerizo, Manuel; Ochoa, Victoria; Berdugo, Miguel; Gozalo, Beatriz; Gallardo, Antonio
Abstract: Dryland ecosystems account for ca. 27% of global soil organic carbon (C) reserves, yet it is largely unknown how climate change will impact C cycling and storage in these areas. In drylands, soil C concentrates at the surface, making it particularly sensitive to the activity of organisms inhabiting the soil uppermost levels, such as communities dominated by lichens, mosses, bacteria and fungi (biocrusts). We conducted a full factorial warming and rainfall exclusion experiment at two semiarid sites in Spain to show how an average increase of air temperature of 2–3 °C promoted a drastic reduction in biocrust cover (ca. 44% in 4 years). Warming significantly increased soil CO2 efflux, and reduced soil net CO2 uptake, in biocrust‐dominated microsites. Losses of biocrust cover with warming through time were paralleled by increases in recalcitrant C sources, such as aromatic compounds, and in the abundance of fungi relative to bacteria. The dramatic reduction in biocrust cover with warming will lessen the capacity of drylands to sequester atmospheric CO2 . This decrease may act synergistically with other warming‐induced effects, such as the increase in soil CO2 efflux and the changes in microbial communities to alter C cycling in drylands, and to reduce soil C stocks in the mid to long term.